Simulation of magnetic dipole and dual stratification in radiative flow of ferromagnetic Maxwell fluid. Issue 4 (April 2019) - Ijaz, Misbah; Ayub, Muhammad
Abstract: Theoretical investigation is performed to explore the novel aspects of nonlinear thermal radiation and non-uniform heat source/sink for chemically reactive flow of ferromagnetic Maxwell liquid over a permeable stretching sheet. Buongiorno model is employed to include Brownian motion and thermophoresis effects. The novelty of the existing study is to account the effect of binary chemical reaction, viscous dissipation, thermal and solutal stratification for ferromagnetic Maxwell fluid. Governing system of nonlinear partial differential equations is transformed into a system of nonlinear ordinary differential equations with the help of apposite similarity transformations. The acquired resulting nonlinear ODEs are solved numerically with the assistance built-in-shooting method (bvp4c). Effects of emanating variables are examined through graphs and tables. It is evident that heat transfer rate enhances with thermal radiation. It is analyzed that temperature upsurges for greater estimations of thermal radiation ( N 1 ∗ ), ferromagnetic ( β ˆ 2 ) and thermophoresis ( N ˆ t ) parameters however it declines for Prandtl number (Pr) and thermal stratified parameter (S₁). Space and temperature dependent heat sinks are more appropriate for cooling purposes.